Islamic Education and Prophetic Social Transformation: Reconstructing Kuntowijoyo’s Thought in the Context of Twenty-First-Century Society - Yulis Sutiani; Mastora; Chusnul Chotimah; Ahsan Hakim (Al-Hikmah: International Journal of Islamic Studies, 2026)
The social transformation of the 21st century marked by globalisation, digitalisation, artificial intelligence disruption, and deepening moral crisis demands a fundamental reconstruction of Islamic educational paradigms. Despite the growing body of research on Islamic education, the integration of Prophetic Social Science (Ilmu Sosial Profetik) as a philosophical foundation for Islamic educational transformation remains underexplored. This study aims to analyse and reconstruct Kuntowijoyo’s thought on Prophetic Social Science as a philosophical basis for developing Islamic education oriented towards social transformation in contemporary society. Employing a qualitative library research design with conceptual analysis and critical hermeneutics as its analytical framework, this study systematically examines primary sources from Kuntowijoyo’s major works alongside peer-reviewed international literature. The findings reveal that the three pillars of humanisation, liberation, and transcendence constitute a coherent and operationalisable framework for Islamic educational transformation. Humanisation strengthens human dignity and social consciousness against dehumanisation; liberation builds critical awareness towards structural injustice; and transcendence provides ethical and spiritual grounding in navigating the dynamics of digital society. The novelty of this study lies in the development of the Transformative Prophetic Islamic Education (TPIE) model  a conceptual framework that systematically integrates these three dimensions into a unified paradigm for individual formation, social transformation, and 21st-century civilisational development. Unlike existing approaches that treat these dimensions separately, the TPIE model offers a comprehensive synthesis that bridges normative Islamic values with emancipatory social praxis. Theoretically, this study expands the discourse of Islamic educational philosophy by integrating the Prophetic Social Science paradigm with critical pedagogy, transformative learning theory, and social transformation theory. Practically, it provides an actionable conceptual framework for developing Islamic educational policies, curricula, and pedagogical practices that are more humanistic, emancipatory, and oriented towards sustainable civilisational development.